PRODUKTIVITAS PEMASANGAN DINDING BATA RINGAN MENGGUNAKAN POLYURETHANE SEBAGAI PEREKAT - Primasiwi Harprastanti; praharseno Fikri; Sukoyo Sukoyo; Wasino Wasino; Diah Wulan (Politeknik Negeri Semarang, 2026)
Time and cost efficiency are critical factors in the construction industry. In the installation of lightweight brick walls, the selection of adhesive type (mortar or polyurethane glue) significantly affects labor productivity. This study aims to empirically validate and compare the installation productivity values, expressed as the number of working hours per square meter (hours/m²), for the two adhesive types. This study employed a controlled experimental method using a 1 m² lightweight brick wall specimen. The two installation methods were tested separately by the same workers to ensure consistency. Installation productivity was calculated based on the ratio of working time to installation area. The results showed that the installation productivity value of lightweight brick walls using mortar was 0.2719 hours/m² (equivalent to 16.32 minutes/m²), whereas the use of polyurethane glue resulted in a productivity value of 0.1264 hours/m² (equivalent to7.58 minutes/m²). This difference indicates a 53.5% improvement in time efficiency when polyurethane glue was used. The increased efficiency was primarily attributed to the elimination of the mixing process and the application of a thinner adhesive layer. The use of polyurethane glue significantly improved the installation productivity of lightweight brick walls. Although polyurethane glue has a higher material cost, its substantially lower installation coefficient makes it an effective option, particularly for projects requiring rapid construction progress, as it can reduce total labor costs and shorten the overall project duration.